2017
DOI: 10.1159/000477359
|View full text |Cite
|
Sign up to set email alerts
|

High Prestroke Physical Activity Is Associated with Reduced Infarct Growth in Acute Ischemic Stroke Patients Treated with Intravenous tPA and Randomized to Remote Ischemic Perconditioning

Abstract: Background: A high prestroke physical activity (PA) level is associated with reduced stroke rate, stroke mortality, better functional outcome, and possible neuroprotective abilities. The aim of the present study was to examine the possible neuroprotective effect of prestroke PA on 24-h cerebral infarct growth in a cohort of acute ischemic stroke patients treated with intravenous tPA and randomized to remote ischemic perconditioning. Methods: In this predefined subanalysis, data from a randomized clinical trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Whether our results reflect an improved cognitive performance fueled by prestroke PA and thus resilience against cognitive decline after stroke, or a protective/“preconditioning” effect of being active before a stroke occurs, is unknown. Unfortunately, baseline cognitive assessment and follow-up neuroimaging with measurement of acute infarct growth/final infarct size were not obtained, but could have proven valuable in exploring both the temporal effects and the mechanistic link behind a potential protective effect of prestroke PA [3, 5]. Further studies are thus needed to disentangle these aspects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether our results reflect an improved cognitive performance fueled by prestroke PA and thus resilience against cognitive decline after stroke, or a protective/“preconditioning” effect of being active before a stroke occurs, is unknown. Unfortunately, baseline cognitive assessment and follow-up neuroimaging with measurement of acute infarct growth/final infarct size were not obtained, but could have proven valuable in exploring both the temporal effects and the mechanistic link behind a potential protective effect of prestroke PA [3, 5]. Further studies are thus needed to disentangle these aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity (PA) is associated with lower stroke risk and mortality as well as a favorable stroke outcome and appears to be a potential general preventive measure against cognitive decline [1][2][3]. Accumulating evidence indicates a possible brain protective effect of prestroke PA [4,5]. The mechanism is largely unknown; however, it seems to go beyond modification of traditional risk factors and may include reduced oxidative damage, inflammation, and capillary dysfunction following a stroke [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the study showed RIPerC to be safe and feasible in the setting of AIS, with the likely benefit of greater tissue survival in the penumbra than the control ( 62 ). Another randomized trial also found that high prestroke physical activity is associated with reduced infarct size after IV tPA treatment only in patients receiving adjuvant RIPerC ( 97 ). While a French multicentric trial of RIC for ischemic stroke within 6 h of symptom onset is currently underway.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Interestingly, it showed for every 60 minutes/day increase in total physical activity there was a reduction of 28% of all-cause mortality related to stroke [ 8 ]. Additional validation for the positive impact of physical activity on stroke risk, as well as the degree of insult, was revealed in a subanalysis of data from a randomized clinical trial done in 2017 where patients with high pre-stroke physical activity (mainly treated with t-PA) had a reduction in the size of infarct growth in 24 hours, as well as the final infarct size [ 9 ].…”
Section: Reviewmentioning
confidence: 99%